2017
DOI: 10.4049/jimmunol.1601066
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial TNF Receptor Signaling Promotes Mucosal Repair in Inflammatory Bowel Disease

Abstract: TNF plays an integral role in inflammatory bowel disease (IBD) as evidenced by the dramatic therapeutic responses in Crohn’s disease (CD) patients induced by chimeric anti-TNF mAbs. However, treatment of CD patients with etanercept, a decoy receptor that binds soluble TNF, fails to improve disease. To explore this discrepancy, we interrogated the role of TNF signaling on Wnt/β-catenin-mediated intestinal stem and progenitor cell (ISC/PC) expansion in CD patients, human cells, and preclinical mouse models. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 43 publications
2
97
0
Order By: Relevance
“…S2) for the inflammatory cytokines interferon-c, IL-17, IL-1b, tumor necrosis factor-a and IL-23, and for the chemokines CXCL1, CCL-19 and CCL-21, which are involved in recruitment of neutrophils, dendritic cells and activated T cells. 12,[27][28][29][30] Both interferona and IL-22 have been reported to have a role in epithelial repair/regeneration and we found lower induction of interferon-a, but higher induction of IL-22 in B6 colonic tissue. No significant induction of IL-6, IL-10, IL-12 and IL-18 was seen in either strain.…”
Section: Dss Induces a Higher Inflammatory Response In B6 Colonssupporting
confidence: 51%
“…S2) for the inflammatory cytokines interferon-c, IL-17, IL-1b, tumor necrosis factor-a and IL-23, and for the chemokines CXCL1, CCL-19 and CCL-21, which are involved in recruitment of neutrophils, dendritic cells and activated T cells. 12,[27][28][29][30] Both interferona and IL-22 have been reported to have a role in epithelial repair/regeneration and we found lower induction of interferon-a, but higher induction of IL-22 in B6 colonic tissue. No significant induction of IL-6, IL-10, IL-12 and IL-18 was seen in either strain.…”
Section: Dss Induces a Higher Inflammatory Response In B6 Colonssupporting
confidence: 51%
“…15 TNF directly activates bcatenin-dependent transcription in the intestine and promotes epithelial regeneration during colitis. 50 We found that TNF represses SIRT2 expression, suggesting that TNFinduces Wnt/b-catenin signaling in IECs through, at least in part, repression of SIRT2 expression. Our findings provide a direct link between SIRT2 and intestinal inflammation.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, production of fibroblast growth factor 2 (FGF2) by Treg cells has recently been shown to synergize with IL‐17 to enhance mechanisms of intestinal epithelial repair . IEC responsiveness to tumour necrosis factor also promotes mucosal repair and healing in individuals with Crohn's disease, human cells and mouse models …”
Section: Iec–immune Cell Crosstalkmentioning
confidence: 99%
“…109 IEC responsiveness to tumour necrosis factor also promotes mucosal repair and healing in individuals with Crohn's disease, human cells and mouse models. 110 Myeloid cells also play key roles in IEC differentiation and function. For instance, perturbations to macrophage-IEC interactions lead to aberrant differentiation of IEC subtypes.…”
Section: Immune Cell Contributions To Iec Differentiation and Functionmentioning
confidence: 99%